Assessment of Patients’ Knowledge, Attitude, and Compliance with the Appointment System in the Outpatient Department of University College Hospital, Ibadan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
• IntroductionMissed appointments and poor adherence to scheduled clinic visits remain significant barriers to efficient healthcare delivery in outpatient settings. Appointment systems are designed to optimize patient flow, minimize wait times, and improve patient satisfaction, but their effectiveness is often undermined by patients’ knowledge and attitudes. This is particularly relevant in tertiary health institutions where patient load is high and resource planning is critical.ObjectiveThis study assessed the level of compliance with the appointment system among patients attending outpatient clinics at the University College Hospital (UCH), Ibadan. It also examined the relationship between respondents’ knowledge of the appointment system and their attitudes, and explored factors influencing appointment adherence.Method of Data AnalysisA descriptive cross-sectional study was conducted among 160 outpatients selected using a systematic sampling technique. Data were collected through a structured questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. Descriptive statistics such as frequencies and percentages summarized the data, while Chi-square tests were used to determine the association between knowledge levels and patients’ attitudes. Statistical significance was set at p